Design and Implement of Infrared Thermography Detection System Excited by Pulsed Flash Lamp - Yang, Zheng-Wei; Luo, Qian; Tian, Gan; Zhang, Wei; Zhu, Jie-Tang (Manufacturing Technology Journal, 2015)
Detection system of infrared thermography technology was designed, taking a non-refrigeration focal plane infrared camera and the pulse flash heating system with high energy as the core. Combining with the performance parameters and structure features of the hardware equipment, integrated control system was designed. Meantime, the cover and reflector for the detection system were fabricated, which improved the uniformity and the utilization rate of energy for the thermal excitation source of the flash lamp. Based on the Delphi program, control, acquisition, processing and analysis system for the infrared image sequence were developed. And defect identification software was also researched which could implement the quantitative calculation and analysis for the parameters of defect size, location, perimeter, area and depth. Finally, experiments for metal and composite with flat bottom defects were carried out by the use of the detection system proposed in this study. The results show that the detection system has the advantages of well controllable performance, convenient operation, perfect detection effect, powerful image processing functions, which can meet the testing demand for engineering application.
Keywords: Pulsed flash lamp; Infrared thermography; Design of the detection system